Effect of migration patterns on maternal genetic structure: A case of Tai-Kadai migration from China to Thailand - Jatupol Kampuansai (2018)
© 2017 The Japan Society of Human Genetics All rights reserved. The migration of the Tai-Kadai speaking people from southern China to northern Thailand over the past hundreds of years has revealed numerous patterns that have likely been influenced by routes, purposes and periods of time. To study the effects of different migration patterns on Tai-Kadai maternal genetic structure, mitochondrial DNA hypervariable region I sequences from the Yong and the Lue people having well-documented histories in northern Thailand were analyzed. Although the Yong and Lue people were historically close relatives who shared Xishuangbanna Dai ancestors, significant genetic differences have been observed among them. The Yong people who have been known to practice mass migration have exhibited a closer genetic affinity to their Dai ancestors than have the Lue people. Genetic heterogeneity and a sudden reduced effective population size within the Lue group is likely a direct result of the circumstances of the founder effect.